This article is… Consumer reactions to unfinished teasers for digital content - Mandler, Timo; Cziehso, Gerrit P.; Schäfers, Tobias; Kupfer, Ann‐Kristin; Mafael, Alexander (Psychology & Marketing)
To preview digital content and arouse consumers' interest, online providers often use short teasers designed in an unfinished form, such that the teaser begins a new sentence but does not finish it. These teasers aim to create curiosity and trigger consumption of the advertised content. However, we reveal that consumers' reactions to unfinished teasers are not always positive. The results from a qualitative pilot study and five experimental studies show that consumers react negatively to unfinished teasers for paid content, as demonstrated by reduced purchases. This effect reverses for free content, in that unfinished teasers lead to more consumption. We explain this reversal by showing that the barrier associated with paid content (i.e., the payment requirement) activates consumers' persuasion knowledge and suppresses any positive curiosity‐induced effects, which does not occur when content is available for free. These findings offer novel insights into the complexity of consumers' reactions to prevalent advertising techniques designed to promote content consumption in digital marketplaces.